2021
DOI: 10.1159/000517185
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol Exerts Cardioprotective Effect in Rheumatoid Arthritis by Inhibiting TLR2/HMGB1 Signaling Pathway-Mediated Autophagy

Abstract: <b><i>Objective:</i></b> Rheumatoid arthritis (RA) is a kind of chronic inflammatory disease characterized by the release of inflammatory cytokines and cardiomyocyte apoptosis, which lead to increased riskfor heart diseases. This study aims to explore the possible effect and mechanism of Celastrol on RA induced cardiac impairments in rats. <b><i>Methods:</i></b> Collagen induced RA wistar rat models (CIA) were established for the measurement on secondary foot swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…A related study found that celastrol could promote autophagy in vitro and in vivo to protect chondrocyte ( Feng et al, 2020 ). Although celatrol has a powerful anti-inflammatory effect, few studies have examined whether such effects are brought out by inhibiting innate immunity, especially TLR2, which has only been reported in multiple sclerosis and RA ( Abdin and Hasby, 2014 ; Lu et al, 2021 ). Furthermore, whether celastrol can regulate TLRs-mediated innate immunity in OA has never been investigated to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A related study found that celastrol could promote autophagy in vitro and in vivo to protect chondrocyte ( Feng et al, 2020 ). Although celatrol has a powerful anti-inflammatory effect, few studies have examined whether such effects are brought out by inhibiting innate immunity, especially TLR2, which has only been reported in multiple sclerosis and RA ( Abdin and Hasby, 2014 ; Lu et al, 2021 ). Furthermore, whether celastrol can regulate TLRs-mediated innate immunity in OA has never been investigated to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…As a valuable inhibitor of NF-κB signaling pathway, celastrol shows anti-inflammatory and bone protective effects in the adjuvant-induced arthritis model ( Cascao et al, 2020 ). Moreover, it has been found that celastrol plays a cardioprotective role in rheumatoid arthritis by inhibiting autophagy mediated by TLR2/HMGB1 signaling pathway ( Lu et al, 2021 ). Compared with autoimmune arthritis, OA is mainly characterized by chronic, relatively low-grade inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…The inflammatory role of extracellular HMGB1 has attracted extensive attention both nationally and internationally [16]. Follow-up studies have shown that HMGB1, which enters the extracellular medium, can act as an important inflammatory mediator in the development of various diseases, such as sepsis, arthritis, and ischemiareperfusion injury [17][18][19]. In SCII, HMGB1 can promote oxidative stress and inflammatory damage [20].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, HMGB1‐elevated secretions have been speculated to trigger dendritic cell and macrophage antigen‐presenting abilities by upregulating major histocompatibility complex II (MHC II), CD83, CD80, and CD86 expression on macrophage surfaces. Consequently, this leads to induction of dendritic cell maturation, activation of T‐helper cells and B lymphocytes, and differentiation of proliferating CD4 + T cells to Th2 and Th17 cells 27–32 . Although BD patients have reportedly elevated the expression levels of HMGB1 compared with healthy controls, controversy about the correlation between HMGB‐1 expression and the Behçet's disease current activity form and Behçet's syndrome activity score 33,34 .…”
Section: Damps and Autoimmune Diseasesmentioning
confidence: 99%